Estudo de propagação de plásmons de superfície em grafeno e realização de portas lógicas OR, AND e XOR - Aguiar, Antônio Francisco (2017)
This work aims to study devices based on graphene in order to obtain logic gates. The model is based on graphene immersed nanofits in dielectric substrate, constructed in such a way that there is coupling of surface plasmon polaritons (SPPs) between sheets of graphene. An interferometric device was proposed as a function of the conductivity of the graphene nanofits and of the geometric dimensions. It was made a numerical analysis of the behavior of the SPPs modes in relation to their chemical potential, as well as a scan of geometric parameters of the device in order to obtain the necessary configurations to perform the logical AND/OR/XOR functions for OOK modulation. The results showed that the lowest extinction level obtained at the proposed gates outputs, referring to the ON state (logical bit 1), was - 4.75 dB. While the OFF state (logical bit 0), the highest extinction level was -11.29 dB. For the OR gate presented higher transmission and coupling efficiency, around -4 dB, for a chemical potential of 0.229 eV for the graphene embedded in a silica substrate with relative permittivity of 2.1. In the AND gate the transmission performance was approximately -5 dB in the coupling region, when the two input channels are ON. This proves the efficiency of graphene plasmon-based logic gates with a minimum average extinction ratio between the 6 dB OFF/ON states for all logic function types.